A Multidimensional Approach in Assessing Geographical Indication Product Sustainability: Salak Pondoh Sleman - Rizky Brisha Nuary; Mochammad Maksum; Anggoro Cahyo Sukartiko (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2022)
Salak Pondoh Sleman (SPS) is an exotic fruit which has geographical indication certification, a sign indicating the unique characteristics inherent in a product due to the influence of its geographical origin. Its unique characteristics can only be found in certain areas. Thus, it is necessary to consider the concept of sustainable agricultural development of the product, involving several dimensions such as environmental, organizational, and technological. The study aimed to assess the sustainability of SPS as a product with geographical indication certification and identify the most influential sustainability attributes in the selected dimensions. A rapid appraisal method of the multidimensional scaling technique was performed to achieve the objective of this study, further mentioned as RAPSalacca. The result showed that the sustainability level of SPS plantation system was classified as ‘quite sustainable,’ with a sustainability index of 59.83. Furthermore, the sustainability analysis of the selected dimensions denoted the important attributes to the sustainability in each dimension, which is further explained in this paper.